Transitive opportunities for development of logistic potential of the territory (on macro- and meso-levels) - Kugan, Svetlana F. (Journal of the Belarusian State University. Economics, 2019)
The article studies the problems of using transitive possibilities for the development of the logistics potential of territories. The solution of this task involves the development of an appropriate theoretical framework, a methodology for assessing the logistics potential of a territory, considered as an economic resource of a territory from the standpoint of external and internal factors of its implementation. In the context of the country’s integration into the international economic system, the need arises to assess the logistics potential of the regions as an important component of socioeconomic monitoring.